1999
DOI: 10.1080/09540129947875
|View full text |Cite
|
Sign up to set email alerts
|

Caring for people with HIV in Zambia: Are traditional healers and formal health workers willing to work together?

Abstract: This study of traditional healers and formal health workers determined their knowledge and practices in the field of HIV/AIDS and examined their training needs and attitudes to collaboration, in preparation for planning joint training workshops. Several misconceptions concerning symptoms and transmission of HIV disease were found in both groups, particularly among traditional healers. Twenty healers (51%) and four formal health workers (15%) claimed a cure existed for AIDS. The majority of traditional healers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 8 publications
2
39
0
Order By: Relevance
“…Earlier, the inclusion was motivated by the problems of shortage of personnel in the modern sector, the self-reliant character of TM, its cultural sensitivity and its therapeutic value [2,8,9]. Presently, while the above reasons remain valid, the increasing social devastations by the AIDS pandemic in poorly performing health care systems confirm the need of involving the traditional health sector [10][11][12].…”
Section: Introductionmentioning
confidence: 96%
“…Earlier, the inclusion was motivated by the problems of shortage of personnel in the modern sector, the self-reliant character of TM, its cultural sensitivity and its therapeutic value [2,8,9]. Presently, while the above reasons remain valid, the increasing social devastations by the AIDS pandemic in poorly performing health care systems confirm the need of involving the traditional health sector [10][11][12].…”
Section: Introductionmentioning
confidence: 96%
“…Other studies have shown that patients with dental problems visit TH first, before a medical or dental practitioner (Burnett ,1999;Peltzer et al 2006;Maclean and Bannerman, 1982 ). Maclean and Bannerman (1982) found that a higher number of older people visited TH than the younger age groups.…”
Section: Continued Existence Of Tm and Oral Health Seeking Behaviour mentioning
confidence: 99%
“…It is further argued that collaboration with THPs has a potential of fostering value and respect of the contributions of THPs in the prevention of HIV and AIDS and also increase resources for HIV and AIDS prevention (Mngqundaniso and Peltzer, 2008;Burnett et al, 1999). Effective collaboration represented by skilled THPs linked to referral facilities could create a complementary HIV and AIDS care system that will be of great benefit to patients and communities (Kayombo et al, 2007;Homsy et al, 2004a;King and Homsy, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In Sub-Saharan Africa, traditional health practitioners (THPs) far outnumber biomedicine health practitioners (BHP), it is estimated that one BHP treats about 20,000 patients while one THP treats about 400 patients (UNAIDS, 2002;WHO, 2002;Burnett et al, 1999;Holmsy and King, 1996). Given WHO's estimation that about 80% of the population throughout Africa relies primarily on traditional medicine for their primary health-care needs, and that patients consult both BHPs and THPs for HIV care.…”
Section: Introductionmentioning
confidence: 99%